A MODEL FOR ASSESSMENT OF TELEMEDICINE APPLICATIONS: MAST - Kidholm, Kristian; Ekeland, Anne Granstrøm; Jensen, Lise Kvistgaard; Rasmussen, Janne; Pedersen, Claus Duedal; Bowes, Alison; Flottorp, Signe Agnes; Bech, Mickael (International journal of technology assessment in health care, 2012)
Objectives: Telemedicine applications could potentially solve many of the challenges faced by the healthcare sectors in Europe. However, a framework for assessment of these technologies is need by decision makers to assist them in choosing the most efficient and cost-effective technologies. Therefore in 2009 the European Commission initiated the development of a framework for assessing telemedicine applications, based on the users’ need for information for decision making. This article presents the Model for ASsessment of Telemedicine applications (MAST) developed in this study. Methods: MAST was developed through workshops with users and stakeholders of telemedicine. Results: Based on the workshops and using the EUnetHTA Core HTA Model as a starting point a three-element model was developed, including: (i) preceding considerations, (ii) multidisciplinary assessment, and (iii) transferability assessment. In the multidisciplinary assessment, the outcomes of telemedicine applications comprise seven domains, based on the domains in the EUnetHTA model. Conclusions: MAST provides a structure for future assessment of telemedicine applications. MAST will be tested during 2010–13 in twenty studies of telemedicine applications in nine European countries in the EC project Renewing Health.